ANALISIS PENGARUH KUALITAS PELAYANAN KERETA API TERHADAP KEPUASAN PENUMPANG PADA PT. KERETA API INDONESIA (PERSERO) WILAYAH SUB DIVISI REGIONAL III.1 KERTAPATI PALEMBANG - Nur Even (JURNAL KOMPETITIF, 2013)
ABSTRACT Analysis Influence Service Quality Train Against Gratification passengers on PT. (Indonesia train persero) Regions Sub-Division Regional III.1 Kertapati Palembang. This research study analysis influence service quality passenger train against complacence PT. (Indonesia train persero) Regions Sub-Division Division Regional III.1 Kertapati Palembang. Implementation of the research conducted during approximately four (4) months including designing, implementing and reporting the results of this research. This case study research aims to know the influence analysis of service quality of railway passenger satisfaction on a Train PT. Indonesia (Persero) Regional Division III Sub Area 1 Kertapati in Palembang. Based on the number of passengers the train PT. Indonesia (Persero) Sub Regional Division III. 1 Kertapati in Palembang that consists of 2 lines of the Palembang- Lubuk Linggau dan Palembang – Tanjung Karang in 2011 gained population was 1.550.310 passengers. Then be sampled as many as 100 people. Of research results obtained by a regression Coefficient regression Coefficients that reability is 0.566, meaning that every one unit of skorreability will increase rail passenger satisfaction scores of 0.566. The regression coefficient is the responsiveness, meaning each addition 0,070 one unit of skorresponsiveness will increase rail passenger satisfaction scores for 0,070. The regression coefficient is the responsiveness, meaning each addition 0,083 one unit of skorassurance will increase rail passenger satisfaction scores for 0,083. The regression coefficient is 0,105 emphaty, meaning that every one unit of skoremphaty will increase rail passenger satisfaction scores for significant rate 0,105 of 5%, multiple regression equation is thus: Ŷ = 4,913 + 0,093 X1 + 0,522 X2 + 0,070 X3 + 0,083X4 + 0,105X5 + e. Implementation, in order to Train Indonesia PT. (Persero) Regional Division III Sub Area 1 Kertapati in Palembang further improve service quality for passengers on longer trains are always feel satisfaction in the services provided by PT Railway Indonesia (Persero). Keywords: the quality of service train, satisfaction passengers